Effects of Risperidone and Aripiprazole on Serum Levels of Prolactin, Testosterone and Estradiol in Female Patients with Schizophrenia - Jiang, Xiao-Jia; Wu, Fu-Xi; Zhang, Jian-Ping; Shi, Lei; Hu, Jin-Qing; Zhu, Hai-Zhen; Xiao, Bing; Lin, Wei-Cheng; Wen, Yu-Guan; Shang, De-Wei (Drug Research, 2018)
Objective To evaluate the effects of treatment with risperidone and aripiprazole on serum prolactin, testosterone and estradiol levels in female patients with schizophrenia in China.Methods In the retrospective study, Data were collected and included prolactin, testosterone and estradiol levels of 30 female patients with risperidone monotherapy. In the prospective study, Another 30 female schizophrenic patients were randomized to receive risperidone or adjunctive aripiprazole for six weeks. Serum prolactin, testosterone and estradiol levels were measured.Results Serum prolactin, testosterone and estradiol levels in both studies were significantly decreased after risperidone treatment compared with baseline (P<0.05), and prolactin levels remained at a high level. Serum prolactin levels in the adjunctive aripiprazole group were significantly decreased after treatment compared with baseline in the prospective study (P<0.05). Doses of 5 mg and 10 mg of adjunctive aripiprazole achieved the same efficacy at the end of treatment.Conclusions Risperidone treatment decreased serum testosterone and estradiol levels. Adjunctive aripiprazole relieved hyperprolactinemia, but had no effect on testosterone or estradiol levels. Adjunctive aripiprazole at a dose of 5 mg is recommended for clinical use.
Keywords: schizophrenia; risperidone; aripiprazole; prolactin; testosterone; estradiol